FORMATION OF SEGMENTED NORMAL FAULTS: A 3-D PERSPECTIVE - Walsh J.J.; Bailey W.R.; Childs C.; Nicol A.; Bonson C.G. (My University, 2003)
The interpretation of fault kinematics from geometric data is an essential step in developing an understanding of the growth of fault systems. Constraints on fault geometry are, however, often restricted to 2-D maps or cross-sections. In this article we consider the extent to which kinematic interpretations of faulting benefit from a 3-D, rather than 2-D geometrical perspective. Concentrating on relay zones and segmented normal fault arrays, we suggest that very different interpretations of their evolution arise from the recognition that the propagation directions of faults, and fault segments, will rarely be contained within the inspection plane of 2-D data. A 3-D perspective favours an interpretation in which the segments of a fault array are kinematically interrelated from their initiation. Individual segments in such systems may link into a single fault surface out of the plane of inspection or may be unconnected in 3-D. We argue that this interpretation, which conflicts with the often suggested model of incidental overlap of originally isolated faults, should be the preferred model for the generation and growth of segmented normal fault arrays.
Keywords: SEGMENTED NORMAL FAULT; FAULT PROPAGATION; FAULT GROWTH